Endovascular versus surgical treatment for improvement of oculomotor nerve palsy caused by unruptured posterior communicating artery aneurysms. (5th March 2020) - Signorelli, Francesco; Pop, Raoul; Ganau, Mario; Cebula, Helene; Scibilia, Antonino; Gallinaro, Paolo; Zaed, Ismail; Todeschi, Julien; Lefevre, Etienne; Nannavecchia, Beniamino; Severac, Francois; Coca, Hugo Andres; et al.
Abstract : Background: There is no consensus regarding the best treatment option for unruptured aneurysms of the posterior communicating artery (PCom) presenting with oculomotor nerve palsy (ONP). We aimed to assess predictors of ONP recovery in a multicenter series of consecutive patients. Materials and methods: A retrospective review of prospective databases in three tertiary neurosurgical centers was carried out, selecting patients with ONP caused by unruptured PCom aneurysms, treated by surgical clipping or embolization, between January 2006 and December 2013. Patient files and imaging studies were used to extract ophthalmological assessments, treatment outcomes, and follow-up data. Predictors of ONP recovery during follow-up were explored using univariate and multivariate analyses. Results: We identified 55 patients with a median ONP duration before treatment of 11 days (IQR 4.5–18); the deficit was complete in 27 (49.1%) and incomplete in 28 (50.9%) cases. Median aneurysm size was 7 mm (IQR 5–9). Twenty-four (43.6%) patients underwent surgical clipping and 31 (56.4%) embolization as the primary treatment. Overall, ONP improved in 40 (72.7%) patients and persisted/recurred in 15 (27.3 %). Surgery, interval to complete treatment <4 weeks, aneurysm recurrence during follow-up, and retreatment during follow-up were significantly correlated with ONP outcome in the univariate analysis. In the multivariate analysis, independent predictors of ONP improvement were interval to complete treatment <4 weeks (OR 5.15, 95% CI 1.37 to 23.71, p=0.015) and aneurysm recurrence during follow-up (OR 0.1, 95% CI 0.02 to 0.47, p=0.003). Conclusion: There was no significant difference in ONP recovery between surgical clipping and embolization. The best predictor for ONP recovery was timely, complete, and durable aneurysm exclusion.